Testing uncovered interest parity: A continuous-time approach - Antonio Diez de los Rios; Enrique Sentana (Bank of Canada, 2007)
Nowadays researchers can choose the sampling frequency of exchange rates and interest rates. If the number of observations per contract period is large relative to the sample size, standard GMM asymptotic theory provides unreliable inferences in UIP regression tests. We specify a bivariate continuous-time model for exchange rates and forward premia robust to temporal aggregation, unlike the discrete time models in the literature. We obtain the UIP restrictions on the continuoustime model parameters, which we estimate efficiently, and propose a novel specification test that compares estimators at different frequencies. Our empirical results based on correctly specified models reject UIP.
Keywords: F31; G15; 330; Exchange rates; Econometric and statistical methods; Devisentermingeschäft; Zinsparität; Theorie